Biosynthesis of chlorophyll-binding proteins in cyanobacteria - Bučinská, Lenka (Jihočeská univerzita, 2019)
In oxygenic phototrophs, the photosynthetic machinery is located in thylakoid membrane (TM), a specialized endogenous membrane system. How TM are synthesized remains however mostly unknown. The aim of this thesis was to clarify a link between the synthesis of chlorophyll (Chl)-binding proteins, the main protein component of TM, and the formation of TM system in the model cyanobacterium Synechocystis PCC 6803. During the project, the analysis of TM under various growth conditions and in Chl-deficient mutants has demonstrated that a sufficient amount of de novo produced Chl molecules is crucial for the TM biogenesis. Particularly, the synthesis of the photosystem II subunit CP47 and trimeric photosystem I appeared to be sensitive to a shortage in de novo made Chl molecules. Interestingly, a specialized ribosome-binding protein (Pam68) has been identified to facilitate the insertion of Chl molecules into CP47. The synthesis of Chl-proteins and the biogenesis of TM have been further explored in cells recovering from long-term nitrogen depletion. Using this approach, it was possible to identify a large structure in the cell cytosol, which is very likely the site of TM biogenesis, and to correlate the appearance of this structure with the restored biogenesis of Chl-binding proteins.
Biosynthesis of chlorophyll-binding proteins in cyanobacteria
Keywords: Synechocystis PCC 6803; chlorophyll-binding proteins; chlorophyll biosynthesis; thylakoid membrane; biogenesis center; assembly factors; Pam68; Synechocystis PCC 6803; chlorophyll-binding proteins; chlorophyll biosynthesis; thylakoid membrane; biogenesis center; assembly factors; Pam68